Measuring the user experience collecting, analyzing, and presenting usability metrics - Tullis, Tom (Thomas).; Albert, Bill (William) (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2008)
Effectively measuring the usability of any product requires choosing the right metric, applying it, and effectively using the information it reveals. Measuring the User Experience provides the first single source of practical information to enable usability professionals and product developers to do just that. Authors Tullis and Albert organize dozens of metrics into six categories: performance, issues-based, self-reported, web navigation, derived, and behavioral/physiological. They explore each metric, considering best methods for collecting, analyzing, and presenting the data. They provide step-by-step guidance for measuring the usability of any type of product using any type of technology. . Presents criteria for selecting the most appropriate metric for every case. Takes a product and technology neutral approach . Presents in-depth case studies to show how organizations have successfully used the metrics and the information they revealed.
Introduction; Background: Data Types; Sampling Size; Experimental Design; Data Analysis. Overview of Usability Metrics: Types of Metrics; Methods and Metrics; Summative vs. Formative; Choosing Appropriate Metrics. Performance Metrics: Task Success; Completion Time; Errors; Efficiency (clicks, pages, steps, etc.). Issues-Based Metrics: What is a Usability Issue; Severity Ratings; Test Biases; Reporting Positive Issues. Peferential-Based Metrics: Satisfaction; Ease of Use, Usefulness; Expectations; Standard Questionnaires. Web Navigation Metrics: Web-page Click-through Rates; Web page Abandonment Rates. Derived Metrics: Task-based; Aggregate. Observational Metrics: Eye Movements; Stress; Facial Expressions; Other Observational Metrics. Case Studies. Special Topics: Six Sigma and Usability; Automated Methods; Discount Techniques; Server Log Analysis; A/B Testing. Conclusion: Communication to Management; Cost Justification; Industry Trends.
Includes bibliographical references and index.
Keywords: User interfaces (computer systems).; User interfaces (Computer systems) -- Measurement; Measurement; Technology assessment; Electronic books